A combined RAD-Seq and WGS approach reveals the genomic basis of yellow color variation in bumble bee Bombus terrestris - Sarthok Rasique Rahman; Jonathan Cnaani; Lisa N. Kinch; Nick V. Grishin; Heather M. Hines (Scientific Reports, 2021)
Abstract Bumble bees exhibit exceptional diversity in their segmental body coloration largely as a result of mimicry. In this study we sought to discover genes involved in this variation through studying a lab-generated mutant in bumble bee Bombus terrestris, in which the typical black coloration of the pleuron, scutellum, and first metasomal tergite is replaced by yellow, a color variant also found in sister lineages to B. terrestris. Utilizing a combination of RAD-Seq and whole-genome re-sequencing, we localized the color-generating variant to a single SNP in the protein-coding sequence of transcription factor cut. This mutation generates an amino acid change that modifies the conformation of a coiled-coil structure outside DNA-binding domains. We found that all sequenced Hymenoptera, including sister lineages, possess the non-mutant allele, indicating different mechanisms are involved in the same color transition in nature. Cut is important for multiple facets of development, yet this mutation generated no noticeable external phenotypic effects outside of setal characteristics. Reproductive capacity was reduced, however, as queens were less likely to mate and produce female offspring, exhibiting behavior similar to that of workers. Our research implicates a novel developmental player in pigmentation, and potentially caste, thus contributing to a better understanding of the evolution of diversity in both of these processes.